Dutch healthcare professionals inadequately perceived if three‐ and four‐year‐old preschool children were overweight. (20th January 2016) - Bocca, Gianni; Corpeleijn, Eva; Broens, Jasper; Stolk, Ronald P.; Sauer, Pieter J.
Abstract: Aim: We studied whether healthcare professionals adequately perceived if preschool children were overweight and whether this was influenced by their own body mass index (BMI). Methods: We sent 716 Dutch healthcare professionals questionnaires containing seven pictures and seven sketches of three‐ and four‐year‐old children showing body weights from underweight to morbidly obese. The professionals rated the pictures on a five‐point scale from too heavy to too light and chose the sketch that they felt best depicted the child's body shape. They also reported their own height and weight and their BMI was calculated. Results: Of the 716 questionnaires, 346 (48.3%) were returned with complete information and analysed. Healthcare professionals mostly chose sketches that showed children as being lighter than they really were. Depending on their own BMI group, the overweight child was perceived as having a normal weight by 74–79% of the healthcare professionals. The obese children were rated correctly by 44–52% of the professionals, but 14–15% said their weight was normal. The morbidly obese child was adequately assessed by 93–98% of the professionals. Conclusion: Healthcare professionals inadequately perceived whether three‐ and four‐year‐old children were overweight and this may have hindered early interventions, leading to overweight children becoming overweight adolescents.